Improving Socio-Emotional Competencies Using a Staged Video-Based Learning Program? Results of Two Experimental Studies - Knigge, Michel; Krauskopf, Karsten; Wagner, Simon (Frontiers in Education, 2019)
Relationship quality between teachers and their students are a critical aspect for wellbeing and effective learning in school. Accordingly, teacher training should promote competencies for creating and maintaining positive relationships in the classroom. The Helga-Breuninger-Foundation developed a video-based online training (Intus3) that intends to focus on student teachers’ interpersonal competencies by reflecting on staged videos. Although this training is well designed, there is only little empirical evidence in general and so far no experimental research investigating the effects of Intus3. Accordingly, we investigated whether this program is able to improve the capacities of student teachers’ interpersonal competencies, affective well-being and affective attitudes towards challenging students. We conducted two randomized experimental studies (n1=132, n2=242) within lectures in teacher education at the University of Potsdam introducing the basics of inclusive education in two consecutive semesters. We compared groups first working with Intus3 to waiting control groups that wrote an expository text based on empirical research discussing the relevance of teacher-student-relationships with a longitudinal design with four measurement points. Latent change models showed that prior work with Intus3 showed few effects but complex effects in comparison the prior text work groups. In the larger and extended study 2 an increase of empathic concern was significant after the prior work with Intus3. The results will be discussed with the perspective of the potential of further development of online training courses for affective learning for teachers and teacher students.